(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This document summarizes results and details of the study on the estimation of canine and feline populations, with some of their characteristics, in each of the Quindío municipalities under departmental jurisdiction. The collection of information on the populations, plus the analysis of characteristics of coexistence with the human population, responds to a need of the Secretary of Health of the Department of Quindío to include this topic in its Development Plan 2020-2023, responding to the objective of "Promoting the reduction of exposure to environmental, sanitary and biological conditions and risk factors, to mitigate the contingencies and damages produced by transmissible diseases (zoonosis and vectors)".